2001
DOI: 10.1007/978-94-010-0585-2_18
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance in the mosquito Culex pipiens: What have we learned about adaptation?

Abstract: Resistance to organophosphate (OP) insecticide in the mosquito Culex pipiens has been studied for ca. 30 years. This example of micro-evolution has been thoroughly investigated as an opportunity to assess precisely both the new adapted phenotypes and the associated genetic changes. A notable feature is that OP resistance is achieved with few genes, and these genes have generally large effects. The molecular events generating such resistance genes are complex (e.g., gene amplification, gene regulation) potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
160
0
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(171 citation statements)
references
References 71 publications
3
160
0
8
Order By: Relevance
“…Thus ace-1 designates the locus coding for a cholinergic AChE (or AChE1), responsible for OP and carbamate resistance in Cx. pipiens (it was previously named Ace.1; Raymond et al 2001) and ace-2 refers to the second ace locus, not involved in insecticide resistance in Cx. pipiens (previously named Ace.2), its function being unknown in Cx.…”
Section: (A) Strains and Crossesmentioning
confidence: 99%
“…Thus ace-1 designates the locus coding for a cholinergic AChE (or AChE1), responsible for OP and carbamate resistance in Cx. pipiens (it was previously named Ace.1; Raymond et al 2001) and ace-2 refers to the second ace locus, not involved in insecticide resistance in Cx. pipiens (previously named Ace.2), its function being unknown in Cx.…”
Section: (A) Strains and Crossesmentioning
confidence: 99%
“…The stability of insecticide resistance was found to be the result of subsequent modification of the insect genome (Roush and McKenzie, 1987;McKenzie, 1996;Guillemaud et al, 1998;Raymond et al, 2001). In the sheep blowfly, Lucilia cuprina, there is a fitness cost associated with an allele coding for resistance to diazinon.…”
Section: Discussionmentioning
confidence: 99%
“…The genes involved in the resistance of the mosquito Culex pipiens to organophosphate insecticides are costly in fitness terms. However, at one resistance locus, a reduction of cost, driven by allele replacement and not by selection of modifiers has been observed (Guillemaud et al, 1998;Raymond et al, 2001). If such modifier genes or allele replacement occurred in T. castaneum malathion-specific resistance, due to the intensive selective pressure with malathion, the increased fecundity of resistance insects may be explained as a pleiotropic effect of the modifier gene or the less costly resistance allele; giving them a reproductive advantage compared to susceptibles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…antibiotic resistance) to mammals. A well-known example comes from insecticide (organophosphate) resistance in the mosquito Culex pipiens caused by a modified acetylcholinesterase (Raymond et al, 2001). Lenormand et al (1999) showed that the frequency of 'resistance' alleles was higher in organophosphate-treated areas, and tended to decrease with distance from those treated sites.…”
Section: Introductionmentioning
confidence: 99%